2023
DOI: 10.21203/rs.3.rs-2578080/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Polyvinyl Alcohol on the Multicomponent Biopolymer/ Hydroxyapatite/Carbonated Hydroxyapatite Composite

Abstract: In this study, the synthesis of composite biomaterials consisting of hydroxyapatite (HA)/carbonated hydroxyapatite (CHA) with polymeric porous scaffolds is reported. Multicomponent biodegradable polymers were applied as the scaffold. These consist of alginate and chitosan. The effect of polyvinyl alcohol (PVA) involvement in the multicomponent polymeric scaffold was also investigated. The scaffold was loaded with HA/CHA, as bone graft materials, at various compositions. Asian moon scallop shell (Amusium pleuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This led to the formation of empty spaces within the material, as the porogen evaporated during the calcination process [ 19 , 21 ]. In this study, the HA material synthesized with a lower PVA concentration demonstrated higher porosity percentage compared to the earlier research conducted with a higher porogen concentration, incorporating PVA, paraffin wax and natural porogen from honeycomb [ 24 , 32 , 44 ].…”
Section: Discussionmentioning
confidence: 75%
“…This led to the formation of empty spaces within the material, as the porogen evaporated during the calcination process [ 19 , 21 ]. In this study, the HA material synthesized with a lower PVA concentration demonstrated higher porosity percentage compared to the earlier research conducted with a higher porogen concentration, incorporating PVA, paraffin wax and natural porogen from honeycomb [ 24 , 32 , 44 ].…”
Section: Discussionmentioning
confidence: 75%
“…Plotting the 3D graph and porosity was done by analyzing the surface area of the SEM images of the scaffold using Origin software. The porosity percentage was obtained by calculating several volume values: solid, integral, and pore volume, based on the 3D graph [3]. The pore distribution in the scaffold was shown in red and solid particles in black.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, when the unbound water in the sample was a little when the freeze-drying method was carried out, the water molecules sublime a little so that the pores formed were also few. A good percentage of porosity for minimal bone growth should be more than 60% [3]. The principle of freeze drying was based on the direct transition of a substance from solid to gaseous form, called sublimation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…English is an important skill that is needed by some people in order to be globalized. (Nurmala Sari & Aminatun, 2021). Therefore, the ability to read is very vital for anyone who is interested in learning English, and teachers of languages other than English place a particular emphasis on reading.…”
Section: Introductionmentioning
confidence: 99%